Interferon therapy and its association with depressive disorders – A review - Lai, Jing Yung; Ho, Jian Xiang; Kow, Audrey Siew Foong; Liang, Gengfan; Tham, Chau Ling; Ho, Yu-Cheng; Lee, Ming Tatt (Frontiers in Immunology, 2023)
Interferons (IFNs) are important in the controlling the innate immune response to virus infections. Besides that, studies have found that IFNs also have antimicrobial, antiproliferative/antitumor and immunomodulatory effects. IFNs are divided into Type I, II and III. Type I IFNs of particular IFN-α is an approved treatment for hepatitis C. However, patients developed neuropsychological disorders during treatment. IFN-α induces proinflammatory cytokines, Indoleamine 2,3-dioxygenase (IDO), oxidative and nitrative stress intensifies body inflammatory response in treatment of chronic inflammatory disease. Intensity of immune response is related with behavioral changes in both animal and human model. Reactive oxygen species (ROS) is important for synaptic plasticity and long-term potentiation (LTP) in hippocampus. However, excess ROS will generate highly reactive free radicals may lead to neurodegeneration. Limbic system regulates memory and emotional response, damage of neurons in this region is correlated with mood disorders. Due to the drawback of the treatment, often patients will not complete the treatment sessions, and this affected their recovery process. However, with proper management, this could be avoided. This review briefly described the different types of IFNs and its pharmacological and clinical usage and also a focus on IFN-α and its implications on depression.